Transitivity and Modality in Sasak Language Conversation (SLC) Texts from a Gender Perspective - Irma Setiawan; Pipit Aprilia Susanti; Ida Ayu Laksmita Sari; M. Aris Akbar (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
The purpose of this study is to explore the construction of gender-based violence in the SLC texts. Gender denotes social roles (not founded on biological or physiological differences) of women and men as perceived by persons or collectives within a given society. The SLC, being a realization of linguistic experience, serves to actualize social roles deemed suitable or unsuitable for women and men. This study concentrates on: 1) The building of gender-based violence derived from the systems of transitivity, modality, and social context in SLC, and (2) The development of precautionary strategies against gender-based violence in SLC. This research utilizes Systemic Functional Linguistics (SFL) theory, concentrating on Halliday’s systems of transitivity, modality, and social context. The methodology used is descriptive qualitative. The data and their sources comprise conversational texts in the SLC collected from public spaces in Mataram City. Data gathering was performed via observation and note-taking, employing non-participant observation and transcription techniques. The tools and analytic procedures are grounded in Halliday’s systemic functional perspective. The results reveal that gender-based violence in the SLC, based on the transitivity system, originates from verbal processes (psychological and physical consequences); based on the modality system, it emerges from a high likelihood or assuredness of action; and based on the social context, it proceeds from patterns of speech participants and discourse devices. The outcomes of this research offer thorough details concerning attempts to prevent gender-based violence in the SLC among the Sasak ethnic community of Lombok Island.